Law as a tool to enable community partnership in wildlife conservation though sustainable tourism - Gitari, Elizabeth (Strathmore University, 2014)
Wildlife Conservation and Management Act, Communities, partnership, co-ownership, sustainable tourism. The wildlife (conservation and management Act) 2013 currently recognizes communities as active participants in wildlife conservation. This is a new concept in law as before its enactment, all community conservation of wildlife took place in a vacuum of legislative support. However, when addressing the participation of communities in wildlife conservation and the issue of wildlife user rights, the Act, assumes that those who own land that is critical for wildlife conservation are the owners of tourism ventures when in fact, in most cases, they are landlords with token appreciation from the real owners of tourism ventures. In most community conservancies that are hailed as promoting sustainable tourism, the benefits that trickle down to the community land owners are all factored into the cost of doing business by the tourism investors, where the profit goes to the investor, who more often than not, is a foreigner. It is time to re-align this and seek out business models that see communities as joint owners of the tourism resources and therefore active participants in promoting sustainable tourism.
Conference paper presented at the 1st African Conference on Sustainable Tourism in Strathmore University, Kenya.
Keywords: Law; Sustainable tourism; Wildlife conservation